2022
DOI: 10.3389/fcell.2022.995013
|View full text |Cite
|
Sign up to set email alerts
|

KRAS protein expression becomes progressively restricted during embryogenesis and in adulthood

Abstract: KRAS mutants are common in many cancers and wild-type KRAS is essential in development as its absence causes embryonic lethality. Despite this critical role in development and disease, the normal expression pattern of KRAS protein is still largely unknown at the tissue level due to the lack of valid antibodies. To address this issue, we used the citrine-Kras mouse model in which the Citrine-KRAS (Cit-K) fusion protein functions as a validated surrogate of endogenous KRAS protein that can be detected on tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…It is also the member of the RAS family to play a crucial role in early embryonic development ( Alves et al, 2019 ). Previous studies demonstrated that KRAS was indispensable for development and its absence could lead to embryo lethality ( Minati et al, 2022 ). Other research indicated that KRAS -deficient mouse embryos develop sever growth defects and die in utero around E15.5.…”
Section: Discussionmentioning
confidence: 99%
“…It is also the member of the RAS family to play a crucial role in early embryonic development ( Alves et al, 2019 ). Previous studies demonstrated that KRAS was indispensable for development and its absence could lead to embryo lethality ( Minati et al, 2022 ). Other research indicated that KRAS -deficient mouse embryos develop sever growth defects and die in utero around E15.5.…”
Section: Discussionmentioning
confidence: 99%